Premature Sperm Activation and Defective Spermatogenesis Caused by Loss of spe-46 Function in Caenorhabditis elegans - Liau, Wei-Siang (Public Library of Science, 2013)

(untitled)
Given limited resources for motility, sperm cell activation must be precisely timed to ensure the greatest likelihood of fertilization. Like those of most species, the sperm of C. elegans become active only after encountering an external signaling molecule. Activation coincides with spermiogenesis, the final step in spermatogenesis, when the spherical spermatid undergoes wholesale reorganization to produce a pseudopod. Here, we describe a gene involved in sperm activation, spe-46. This gene was identified in a suppressor screen of spe-27(it132ts), a sperm-expressed gene whose product functions in the transduction of the spermatid activation signal. While spe-27(it132ts) worms are sterile at 25°C, the spe-46(hc197)I; spe-27(it132ts)IV double mutants regain partial fertility. Single nucleotide polymorphism mapping, whole genome sequencing, and transformation rescue were employed to identify the spe-46 coding sequence. It encodes a protein with seven predicted transmembrane domains but with no other predicted functional domains or homology outside of nematodes. Expression is limited to spermatogenic tissue, and a transcriptional GFP fusion shows expression corresponds with the onset of the pachytene stage of meiosis. The spe-46(hc197) mutation bypasses the need for the activation signal; mutant sperm activate prematurely without an activation signal in males, and mutant males are sterile. In an otherwise wild-type genome, the spe-46(hc197) mutation induces a sperm defective phenotype. In addition to premature activation, spe-46(hc197) sperm exhibit numerous defects including aneuploidy, vacuolization, protruding spikes, and precocious fusion of membranous organelles. Hemizygous worms [spe-46(hc197)/mnDf111] are effectively sterile. Thus, spe-46 appears to be involved in the regulation of spermatid activation during spermiogenesis, with the null phenotype being an absence of functional sperm and hypomorphic phenotypes being premature spermatid activation and numerous sperm cell defects.